John F. Kennedy - Randall, Marta (New York : Chelsea House, 1988)
Chronicles the early life, presidential campaign, term in office, and assassination of the thirty-fifth president of the United States.
Includes bibliographical references and index.
Keywords: Kennedy, John F. -- 1917-1963 -- Juvenile literature; Kennedy, John F. -- 1917-1963.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; United States -- Politics and government -- 1961-1963 -- Juvenile literature; United States -- History -- 1961-1969.